Stimulation of C-Kit+ Retinal Progenitor Cells by Stem Cell Factor Confers Protection Against Retinal Degeneration - Chen, Xi; Li, Shanshan; Liu, Xiaoli; Zhao, Jingjie; Wu, Lanting; You, Ran; Wang, Yanling (Frontiers in Pharmacology, 2022)
C-kit/CD117, expressed in a series of tissue-specific progenitor cells, plays an important role in tissue regeneration and tissue homeostasis. We previously demonstrated that organoid-derived c-kit+ retinal progenitor cells can facilitate the restoration of degenerated retina. Meanwhile, we have identified a population of endogenous c-kit+ cells in retinas of adult mouse. However, the exact role of these cells in retinal degeneration remains unclear. Here, we demonstrated that stimulation of endogenous c-kit+ cells by stem cell factor (SCF) conferred protection against retinal degeneration. Retinal degeneration was induced by intravitreal injection of N-methyl-D-aspartate (NMDA). NMDA challenge increased the total number of c-kit+ cells in the retinal ganglion cell layer (GCL), while deregulated the protein level of SCF, which was mainly expressed in Müller cells. Both flash electroretinogram(fERG) and light/dark transition tests showed that intravitreal injection of SCF effectively improved the visual function of NMDA-treated mice. Mechanistically, SCF administration not only prevented the loss of retinal ganglion cells (RGCs), but also maintained the function of RGCs as quantified by fERG. Further, we performed transcriptome sequencing analysis of the retinal cells isolated from SCF-treated mice and the parallel control. Gene Ontology analysis showed that SCF-induced transcriptome changes were closely correlated with eye development-related pathways. Crystallins and several protective factors such as Pitx3 were significantly upregulated by SCF treatment. Our results revealed the role of SCF stimulated c-kit+ cells in the protection of RGCs in NMDA-treated mice, via inhibiting the loss of RGCs. Administration of SCF can act as a potent strategy for treating retinal degeneration-related diseases.